Advances in Databases and Information Systems: 18th East European Conference, ADBIS 2014, Ohrid, Macedonia, September 7 - 10, 2014; proceedings - Manolopoulos, Yannis (Lecture notes in computer science, 2014)
This book constitutes the thoroughly refereed proceedings of the 18th East European Conference on Advances in Databases and Information Systems, ADBIS 2014, held in Ohrid, Macedonia, in September 2014. The 26 revised full papers presented together with one invited talk were carefully selected and reviewed from 82 submissions. The papers are organized in topical sections on data models and query languages; data warehousing; query and data-flow optimization; information extraction and integration; spatial, temporal and streaming data; data mining and knowledge discovery; data organization and physical issues; and data and business processes
Literaturangaben
Keywords: Konferenzschrift; Wissensextraktion; Abfrageverarbeitung; Transaktionssystem; Datenbanksystem; Informationssystem